2005
DOI: 10.1038/labinvest.3700343
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteins from formalin-fixed paraffin-embedded cells by LC-MS/MS

Abstract: There exists a need for robust approaches for tandem mass spectrometry (MS/MS)-based identification of proteins in formalin-fixed paraffin-embedded (FFPE) material. We demonstrate herein the identification of proteins in FFPE material using enzymatic cleavage for extraction of peptides from the FFPE specimen and liquid chromatography (LC) followed by MS/MS. We identified 324 proteins from a 3-year-old FFPE cell-block of a human lymphoma cell line. The identified proteins were assigned to the membrane, cytosol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(146 citation statements)
references
References 24 publications
4
140
2
Order By: Relevance
“…5). We attribute the poor outcome of Glu-C digests for identifying phosphopeptides to the fact that although the average length of peptides generated is indeed in a favorable range (between trypsin and Lys-C), the fragmentation in ETD is impaired, as noted previously for CID (15). database.…”
Section: Resultsmentioning
confidence: 97%
“…5). We attribute the poor outcome of Glu-C digests for identifying phosphopeptides to the fact that although the average length of peptides generated is indeed in a favorable range (between trypsin and Lys-C), the fragmentation in ETD is impaired, as noted previously for CID (15). database.…”
Section: Resultsmentioning
confidence: 97%
“…Although these results are encouraging, there are a number of challenges that must be addressed to develop better and more reproducible techniques for extracting and identifying proteins useful for proteomic analysis from archival FFPE tissue. The study by Crockett et al 5 perhaps best illustrates the current state of our ability to use archival FFPE tissues for proteomic studies. Liquid chromatographytandem mass spectrometry was used to compare proteins identified in a fresh cell lysate to the same cells processed as an FFPE cell plug.…”
mentioning
confidence: 99%
“…[3] demonstrated that the proteins can be extracted from ethanol-fixed and paraffin-embedded tissue, and resolved by 2-DE separation. Recently Shi et al [4] obtained a satisfying overlapping between proteins identified from FFPE and frozen tissues and encouraging results are reported also by Prieto et al [5] and Crockett et al [6] that identified proteins from FFPE enzymatically digested tissues. However, few studies have been pursuing MALDI-TOF imaging MS (MALDI-IMS), the most challenging proteomics analysis application on FFPE section.…”
Section: Introductionmentioning
confidence: 74%